Systematics and molecular phylogeny of the family oscarellidae (homoscleromorpha) with description of two new oscarella species. - Eve Gazave; Dennis V Lavrov; Jory Cabrol; Emmanuelle Renard; Caroline Rocher; Jean Vacelet; Maja Adamska; Carole Borchiellini; Alexander V Ereskovsky (PLoS ONE, 2013)
The family Oscarellidae is one of the two families in the class Homoscleromorpha (phylum Porifera) and is characterized by the absence of a skeleton and the presence of a specific mitochondrial gene, tatC. This family currently encompasses sponges in two genera: Oscarella with 17 described species and Pseudocorticium with one described species. Although sponges in this group are relatively well-studied, phylogenetic relationships among members of Oscarellidae and the validity of genus Pseudocorticium remain open questions. Here we present a phylogenetic analysis of Oscarellidae using four markers (18S rDNA, 28S rDNA, atp6, tatC), and argue that it should become a mono-generic family, with Pseudocorticium being synonymized with Oscarella, and with the transfer of Pseudocorticium jarrei to Oscarella jarrei. We show that the genus Oscarella can be subdivided into four clades, each of which is supported by either a small number of morphological characters or by molecular synapomorphies. In addition, we describe two new species of Oscarella from Norwegian fjords: O. bergenensis sp. nov. and O. nicolae sp. nov., and we compare their morphology, anatomy, and cytology with other species in this genus. Internal anatomical characters are similar in both species, but details of external morphology and particularly of cytological characters provide diagnostic features. Our study also confirms that O. lobularis and O. tuberculata are two distinct polychromic sibling species. This study highlights the difficulties of species identification in skeleton-less sponges and, more generally, in groups where morphological characters are scarce. Adopting a multi-marker approach is thus highly suitable for these groups.